2022
DOI: 10.1001/jamaoncol.2022.4432
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Treatment With Cobimetinib in Patients With Rosai-Dorfman Disease Based on KRAS and MEK Alteration Status

Abstract: ImportanceRosai-Dorfman disease (RDD) is a rare histiocytic neoplasm with recent studies showing alterations in the MAPK pathway, most commonly in the KRAS and MEK genes in about 40% of patients. Reports on the use of MEK-inhibitor therapy in RDD have been limited to small case studies. There are no approved treatments for this neoplasm, and therefore patients with RDD need efficacious treatments.ObjectiveTo study the outcomes after treatment with cobimetinib based on MAPK pathway alterations in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…KRAS and MEK gene alterations are present in approximately 40% of RDD cases. A recent retrospective cohort study demonstrated clinically significant response rates using the MEK inhibitor cobimetinib in KRAS and MEK -variant RDD ( 26 ). BRAF oncogene mutations are a well-established molecular driver and treatment target in other histiocytoses such as Langerhans cell histiocytosis and Erdheim-Chester disease ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…KRAS and MEK gene alterations are present in approximately 40% of RDD cases. A recent retrospective cohort study demonstrated clinically significant response rates using the MEK inhibitor cobimetinib in KRAS and MEK -variant RDD ( 26 ). BRAF oncogene mutations are a well-established molecular driver and treatment target in other histiocytoses such as Langerhans cell histiocytosis and Erdheim-Chester disease ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ALK inhibitor, crizotinib, achieved 90% and 86% ORR and 80% and 36% complete response in anaplastic large-cell lymphoma (ALCL) and inflammatory myofibroblastoma (IMT), respectively. 69 Subsequently, ALK inhibitors were shown to be effective in malignant peritoneal mesothelioma, neuroblastoma, renal cell carcinoma, colorectal cancer, and melanoma. 70 72 The high remission rate of ALK inhibitors for ALK-driven NSCLC, ALCL, and IMT unlocked the “single-target to single-drug” model in the epoch dominated by chemotherapy, which was the most typical pattern of basket trials.…”
Section: Discovery: Clinical Dilemma Prompting An Exploration Of New ...mentioning
confidence: 99%
“…Diamond et al 23 demonstrated an overall response rate (per investigators' defined positron emission tomography [PET] response criteria in solid tumors) of 89% in a cohort of 18 patients, which resulted in FDA approval. In addition, a retrospective study of cobimetinib in RDD demonstrated an overall response rate of 63% 24 .…”
Section: Introductionmentioning
confidence: 99%